Functionalized Gels for Environmental Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is dedicated to the synthesis, characterization, and application of functionalized or doped matrices (e.g., hydrogels, aerogels, or sol–gels) for environmental purposes such as the sensing or removal of different toxic analytes. The chemical functional groups or doping materials, such as noble metal nanostructures, quantum dots, and carbon nanotubes, play several roles, donating further features to the host matrix such as particular optical, mechanical, or electrical properties and interacting with the surrounding environment. In addition, the employment of hosting matrices increases handling and portability and opens new horizons for in situ environmental applications.